STUDI KELAYAKAN PEMANFAATAN LIMBAH SUMPIT UNTUK PEMBUATAN PRODUK PENGISI RONGGA - RONGGA KERTAS PADA UD MUTIARA 9 SERANG BANTEN - Eka Angkasa Putra Agni Hermawan (Universitas muhammadiyah malang, 2015)
This study aims to analyse levels of the feasiblity of the utilization of chopstick waste of the manufacture of filler products cavities. To measure the feasibility some aspects should be considered such as market, marketing, operational, human resources, and financial aspect. The result indicated that all acpect was feasible. The market aspect is feasible because it has high demand. Operation aspect is feasible because of modern technology used. Human resource aspects is feasible because of the there were skills labor own by the company, and financial aspect is also feasible because NPV more than zero and payback period less than estimated period.